2019
DOI: 10.1038/s41598-019-54716-8
|View full text |Cite
|
Sign up to set email alerts
|

Purification and biological activity of natural variants synthesized by tridecaptin M gene cluster and in vitro drug-kinetics of this antibiotic class

Abstract: The flexibility of the adenylation domains of non-ribosomal peptide synthetases (NRPSs) to different substrates creates a diversity of structurally similar peptides. In the present study, we investigated the antimicrobial activity of different natural variants synthesized by tridecaptin M gene cluster and performed the in vitro drug kinetics on this class. The natural variants were isolated and characterized using MALDI-MS and tandem mass spectrometry. All the peptides were studied for their antimicrobial acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Tridecaptin M was tested to assess the effect on the outer membrane of different Gram-negative bacteria. We previously showed that tridecaptin M has weak antimicrobial activity in A. baumannii and was not active against P. aeruginosa [ 39 ]. However, similar to previously reported results, we observed strong permeabilization of the outer membrane in a concentration-dependent manner in all the pathogens as denoted by the increase in fluorescence intensity of N -phenyl-1-naphthylamin (NPN) dye ( Figure 2 a–c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tridecaptin M was tested to assess the effect on the outer membrane of different Gram-negative bacteria. We previously showed that tridecaptin M has weak antimicrobial activity in A. baumannii and was not active against P. aeruginosa [ 39 ]. However, similar to previously reported results, we observed strong permeabilization of the outer membrane in a concentration-dependent manner in all the pathogens as denoted by the increase in fluorescence intensity of N -phenyl-1-naphthylamin (NPN) dye ( Figure 2 a–c).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, unacylated tridecaptin A 1 (without the lipid moiety; Figure 1 ), though ineffective itself, was reported to potentiate (or reduce the minimum inhibitory concentration of) Gram-positive antibiotics in Gram-negative bacteria including Enterobacteriaceae and A. baumannii [ 38 ]. Tridecaptins have very low intrinsic activity against A. baumannii [ 36 , 37 ], but they could still permeabilize the outer membrane very efficiently [ 39 ]. The naturally occurring tridecaptins are active against Enterobacteriaceae but have not been investigated for their potential in combination therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Uptake of N-(1-naphthyl)aniline (NPN) dye by various Gram-negative strains confirmed OM binding by both TriM 1 and M 11 , while DiSC 3 (5) membrane depolarization assays are said to align with previous findings of disruption of the proton motive force. 24,30 Although further mechanism of action studies are required to confirm the cellular interactions responsible for the antimicrobial activity of the TriM variants, this novel class of NRAP-further highlights the potential of the tridecaptins as novel therapeutics for the treatment of stubborn bacterial infections.…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%
“…No clear structure-activity relationship could be drawn from the range of analogues isolated, except that there may exist a synergistic relationship between certain amino acids, such that substitutions may impede activity. 24 The antimicrobial activity across the TriM family (92-98) is comparable to tridecaptin A and its variants such that they are active against Gram-negative E. coli, A. baumannii and even colistin-resistant strains of K. pneumoniae. TriM 11 (98) displayed the most potent antimicrobial activity and was even found to be highly active (MIC = 4 μg mL −1 ) against the polymyxin-resistant bacteria, Proteus mirabilis and Serratia marcescens.…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%
See 1 more Smart Citation